In vitro assessment of hepatoprotective agents against damage induced by acetaminophen and CCl4 - Torres González, Liliana; Waksman Minsky, Noemí Herminia; Muñoz Espinosa, Linda Elsa; Salazar Aranda, Ricardo; Pérez Meseguer, Jonathan; Cordero Pérez, Paula (2017)
Abstract Background: In vitro bioassays are important in the evaluation of plants with possible hepatoprotective effects. The aims of this study were to evaluate the pretreatment of HepG2 cells with hepatoprotective agents against the damage induced by carbon tetrachloride (CCl4) and paracetamol (APAP). Methods: Antioxidative activity was measured using an assay to measure 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging. The in vitro hepatotoxicity of CCl4 and APAP, and the cytotoxic and hepatoprotective properties of silymarin (SLM), silybinin (SLB), and silyphos (SLP) were evaluated by measuring cell viability; activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and lactate dehydrogenase (LDH); total antioxidant capacity (TAOxC); and reduced glutathione (GSH), superoxide dismutase (SOD), and lipid peroxidation (malondialdehyde (MDA) levels). Results: Only SLB and SLM showed strong antioxidative activity in the DPPH assay (39.71±0.85 μg/mL and 14.14±0. 65 μg/mL, respectively). CCl4 induced time- and concentration-dependent changes. CCl4 had significant effects on cell viability, enzyme activities, lipid peroxidation, TAOxC, and SOD and GSH levels. These differences remained significant up to an exposure time of 3 h. APAP induced a variety of dose- and time-dependent responses up to 72 h of exposure. SLM, SLB, and SLP were not cytotoxic. Only SLB at a concentration of 100 μg/mL or 150 μg/mL significantly decreased the enzyme activities and MDA level, and prevented depletion of total antioxidants compared with CCl4. Conclusions: CCl4 was more consistent than APAP in inducing cell injury. Only SLB provided hepatoprotection. AST, LDH, and MDA levels were good markers of liver damage. Keywords: Hepatoprotective, HepG2 cell line, Acetaminophen, Carbon tetrachloride, Silybinin, Silyphos, Silymarin